ARTEFAK BATU PRENEOLITIK SITUS LEANG JARIE: BUKTI TEKNOLOGI MAROS POINT TERTUA DI KAWASAN BUDAYA TOALEAN, SULAWESI SELATAN - Suryatman; Hakim, Budianto; Mahmud, Muh. Irfan; Fakhri; Burhan, Basran; Oktaviana, Adhi Agus; Saiful, Andi Muh.; Syahdar, Fardi Ali (Penerbit BRIN (BRIN Publishing), 2019)
Abstract. The Preneolithic Stone Artefact of Leang Jarie Site: The Oldest Evidence of Maros Point Technology in the Toalean Culture Region, South Sulawesi. Maros Point is one type of flake tool that shows characteristics of the techno-complex Toalean from South Sulawesi. Early emergence of the Toalean Culture phase is still debated, but most experts agree that this tool only appeared no more than 4000 years ago and is positioned include with pottery or Neolithic period. The Maros Point is considered to be made by the early occupants of Sulawesi after the arrival and contact with Austronesian speakers migration in South Sulawesi. The problem is that the results of the latest research are contrary to previous opinions. This paper aims to show new evidence of excavation at the Leang Jarie Site, as the oldest Maros Point technology ca. 8,000 years ago in the Toalean Cultural Region. Maros Point is made simpler with the support flake without using reduction pattern of flake-blade technology. Flakes with an asymmetrical shape can also be utilized as long as it have a pointed and thin tip. The